Mechanical properties of rice husk ash cement mass concrete mixed with discrete steel fibres. - Abiodun, Y. O.; Sijuwola, O.O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The potential use of supplementary cementitious materials in concrete for improving concrete properties has been a growing concern in recent years. This is due to the environmental and health hazards associated with the increase in the use of cement in concrete as a result of infrastructural development all over the world. The effective strengthening of the concrete matrix by reinforcements helps to prevent brittleness that occurs in plain concrete. This study investigated the mechanical properties of randomly distributed discrete steel fibers in Rice Husk Ash-cement matrix and its effect on the strength and performance of concrete. Rice husk was burnt at a controlled temperature of 600°C for 4 hours in an electric furnace to get the rice husk ash. Prescribed mix ratio of 1:2:4 and water-cement ratio of 0.5 were used in all the mixes of rice husk ash cement mass concrete mixed with discrete steel fibres. The parameters varied were Rice Husk Ash content at 0%, 10%, 15%, 20%, and 25% and discrete steel fiber dosage of 0.5kg and 1kg.The mechanical properties of the rice husk ash cement mass concrete mixed with discrete steel fibres were studied through Compressive strength test, Split Tensile test and Flexural test. Results obtained show that the RHA-cement mass concrete mixed with discrete steel fibres reached maximum compressive strength at an optimum value of 10% RHA and 1kg of discrete steel fibres. The highest values for split tensile and flexural strengths were obtained at 10% RHA replacement.